INOCA: Unraveling the pathophysiological mechanisms, non-invasively. (20th July 2021) - Gobbo, MY; Meretta, AH; Sciancalepore, MA; Rosa, D; Corneli, M; Blanco, N; Retamozo, E; Beber, E; Coronel, DS; Perez Balino, NA; Masoli, OH
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: INOCA syndrome (Ischemia with Non-Obstructive Coronary Arteries) is an increasingly frequent finding. One of the proposed causes is microvascular dysfunction (MVD). CZT-SPECT systems quantifies myocardial blood flow (MBF) during rest and after hyperemia. Dipyridamole induced hyperemia is considered endothelium independent whereas cold pressor test (CPT) endothelium dependent. Using both stimuli vasomotor response of endothelium can be evaluated through the analysis of MBF relationship (MBFR): MBF during induced hyperemia/MBF rest. Objectives: To determine the prevalence of microvascular dysfunction in patients with INOCA, through the analysis of non-invasive evaluation MBFR with dipyridamole and CPT. Methods: Dynamic and myocardial perfusion imaging at rest, after dipyridamole (0, 56 mg/kg i.v. in 4 minutes) and CPT (hand immersion during 2 minutes in 4ºC cold water) were performed in 45 patients with INOCA history of using CZT-SPECT system. A MBFR less than 2 was considered abnormal to dipyridamole induced hyperemia and less than 1.5 to CPT induced hyperemia. The presence of an abnormal dipyridamole or CPT MBFR was considered as MVD. Patients with MVD were divided into two groups: Group 1: normal dipyridamole MBFR and abnormal CPT MBFR. Group 2: abnormal dipyridamole MBFR and abnormal CPT MBFR. Comparison between variables were made with Wilcoxon signed rank test. Results: The median age was 59 (32-78) years. Thirty-two patients (71%) were women and the majority (n = 29) were in the menopausal period. The cardiovascular risk factors present were: type 2 diabetes mellitus (n = 4), arterial hypertension (n = 21), smoking (n = 18) and dyslipidemia (n = 25). All patients had normal myocardial perfusion at rest and with both stresses. Thirty-nine patients (87%) presented MVD, 24 (54%) were in the group 1 and 15 (33%) in group 2. (Table 1) Conclusion: The prevalence of MVD was 87 % in patients with INOCA.The use of both stresses made it possible to evaluate different pathophysiological mechanisms of MVD, dependent on smooth muscle and dependent on the endothelium. Evaluation with CPT should be included in INOCA patients because MVD may be present even with preserved MBFR using dipyridamole.